Batik Jambi Cultural Center With An Ecological Architecture Approach (International Journal of Architecture and Urbanism, 2023)
Batik is one of the cultural heritages of Indonesia which has spread to almost all of Indonesia with a different motifs and patterns. The territory of Indonesia which is the largest producer of batik is spread over the Island of Java with a total 87% and the rest is outside the island of Java. One of the largest is in Jambi Province, the center is across the Batanghari river where this area is the residence of the indigenous people of Jambi who generally work as a batik craftsman. Unfortunately, in the city of Jambi itself there is no facility or building that specifically introduces Jambi batik so that it also affects the interest of the Jambi community in the knowledge and attraction of Jambi batik. Therefore, it is necessary to design the Jambi Batik Cultural Center as an educational and recreational place for Jambi batik as a whole with various activities such as batik gallery exhibitions, batik sales, development and training of batik making with a building design approach with the theme of Ecological Architecture that responds to the site location near the area Batanghari river.